Effects of Discovery Learning Assisted by WebGIS Media on Students’ Critical Thinking Skills - Ages Riski Lestari; Nyokro Mukti Wijaya; Novia Fitri Istiawati; Dian Utami (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Critical thinking skills are one of the essential competencies needed by students to face the challenges of 21st-century learning, particularly in geography learning, which requires students to analyze, evaluate, and solve various geographical problems. However, the critical thinking skills of students at SMA Negeri 1 Natar are still relatively low, indicating the need for innovative learning models and media to support the learning process. This study aims to determine the influence of the Discovery Learning learning model and WebGIS media on the critical thinking ability of grade XI students of SMA Negeri 1 Natar. This study uses a quantitative approach with a 2×2 factorial quasi experimental design. The research sample consisted of 141 students who were divided into four treatment classes. The instrument used was a multiple-choice test to measure students' critical thinking skills. Data were analyzed using Two-Way ANOVA. The results showed that the Discovery Learning learning model had a significant effect on critical thinking skills with a significance value of 0.000 (<0.05). WebGIS media also had a significant effect with a significance value of 0.000 (<0.05). However, there was no interaction between the learning model and the learning media, with a significance value of 0.706 (>0.05). The R Square value of 0.323 indicates that the learning model and media together contribute 32.3% to students' critical thinking skills. Thus, Discovery Learning and WebGIS are separately effective in improving students' critical thinking skills in geography learning.